Prevalence of adrenal myelolipoma during abdominal computed tomography at Hospital Universitario San Vicente Fundación - Román González, Alejandro; Agredo Delgado, Valentina; Aristizábal Barón, Julieta; Arizmendy Acosta, Diana (Iatreia, 2018)
Objective: Adrenal myelolipoma is an infrequent benign tumor. Myelolipoma represents 2,6-3 % of all adrenal incidentalomas. This tumor is more frequent in aged individuals. Our aim was to evaluate the prevalence of myelolipoma in patients with adrenal incidentaloma detected by abdominal computed tomography (CT) during 1 year at a university tertiary care hospital. Methods: Retrospective study. All abdominal CT done at the Hospital Universitario San Vicente Fundación, Medellín, Colombia, with or without contrast, were reviewed from 2014 to 2015. Of all adrenal incidentalomas, those with diagnosis of adrenal mielolipoma were further evaluated. The clinical and laboratory data were extracted. Results: 4288 abdominal CT were reviewed in 3709 patients. 108 adrenal incidentalomas were found. Of those, two cases were adrenal myelolipomas. The frequency of mielolipoma presenting as adrenal incidentalomas was 1.85 % with a prevalence in abdominal CT of 0.05 %. The mean age at presentation was 57 years. Both cases were unilateral right masses; the mean size was 31 mm and a mean of -84.5 Hounsfield units. Hormonal studies or surgical management was no performed.Discussion: This study report the prevalence and clinical characteristics of adrenal myelolipoma presenting as adrenal incidentalomas. 1.85 % of adrenal incidentalomas are myelolipomas. To our knowledge, there are no studies in Colombia evaluating the prevalence of this disease in abdominal CT scans. In conclusion, myelolipoma is an infrequent adrenal tumor.